Biomechanical analysis of the trajectory of movement of the center of gravity of an athlete in martial arts - Levitsky A.G. ,; Matveev D.A. ,; Potsipun А.А. ,; Krutoy A.N. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the essence of the process of oscillations of the athlete’s center of gravity when moving using the “shuttle” method and to test the methodology for analyzing the movement of the center of gravity. Methods and structure of the study. The essence of the analysis of oscillatory movements of the center of gravity is to construct the trajectory of the athlete’s movement, as well as graphs of changes in speeds and accelerations of the center of gravity depending on the coordinate. In this case, the graphs are plotted one below the other on the same scale of the coordinate axis. This allows you to visually compare the features of the trajectory of the center of gravity with changes in speed and acceleration. Results and conclusions. Fluctuations in the center of gravity of an athlete during movement using the “shuttle” method represent a movement of the center of gravity from one area of ​​space to another in the forward and backward directions. In this case, the movement trajectories differ from each other. It is advisable to describe such oscillations not by individual parameter values, but by areas of parameter values characteristic of a specific state of the system. The data processing technique used allows us to obtain more complete and visual information about the movement of the athlete’s center of gravity during movement.